Effects of Neem Aqueous Extract (Azadirachta indica) against Aphids and Aphid-borne Virus in Cowpea (Vigna unguiculata L. Walp) - Kareem, Kehinde T.; Olayinka, Rachael B.; Ugwu, Juliana A.; Oduwaye, Olubusola F. (Tanzania Journal of Science, 2022)
Pests and diseases are among the major factors limiting plant growth and yields. Pests are known vectors of pathogens including viruses. Proper management of plant pests is an indirect means of controlling viral diseases in plants. This study aimed at comparing the potential of neem extract and a synthetic insecticide (lambda cyhalothrin) for the management of aphids and Cowpea aphid-borne mosaic virus (CABMV) in five different cowpea (Vigna unguiculata) genotypes and to determine the residual effects of the insecticide in the cowpea grains. The experimental field was laid out in randomized complete block design with three replicates. Treatments included; spraying of cowpea plots with aqueous neem extract and lambda cyhalothrin (LC) twice at foliage stage, once at flowering and podding stages. Control plots were left unsprayed. Data were obtained on growth and yields of cowpea genotypes as well as the pest and virus disease traits. Results of the Analysis of Variance (ANOVA) revealed that variations attributable to genotypes were significant (p ≤ 0.01) for cowpea yields and virus disease traits. Treatments applied influenced the occurrence of pests and virus diseases. Neem extract reduced aphid infestations and virus diseases as much as the insecticide. Ife BPC accumulated a very high level of LC (1.14 ppm) in its grain when compared with the maximum residue level (MRL) for lambda cyalothrin in cowpea seeds. The study concludes that the use of eco-friendly bio-pesticide such as neem aqueous extract is effective for the management of aphids and aphid-borne virus in cowpea fields. Keywords: Aphids; aqueous extract; cowpea; neem; pesticide; virus